Current aspects in immunosensors - Gopinath, S.C.B.; Tang, T.H.; Citartan, M.; Chen, Y.; Lakshmipriya, T. (Elsevier, 2014)
Sensing applications can be used to report biomolecular interactions in order to elucidate the functions of molecules. The use of an analyte and a ligand is a common set-up in sensor development. For several decades, antibodies have been considered to be potential analytes or ligands for development of socalled "immunosensors." In an immunosensor, formation of the complex between antibody and antigen transduces the signal, which is measurable in various ways (e.g., both labeled and label-free based detection). Success of an immunosensor depends on various factors, including surface functionalization, antibody orientation, density of the antibody on the sensor platform, and configuration of the immunosensor. Careful optimization of these factors can generate clear-cut results for any immunosensor. Herein, current aspects, involved in the generated immunosensors, are discussed.